PERUBAHAN TATA KELOLA MARITIM DI WILAYAH KALIMANTAN TIMUR SEBAGAI IBUKOTA BARU - Sri Cempaka Prima; Andri Octapianus Purba; I Wayan Yuliarta; Panji Suwarno (NUSANTARA : Jurnal Ilmu Pengetahuan Sosial, 2020)
The East Kalimantan region is a strategic province because its geographical location is in the middle of Indonesia and is known as the Center of Indonesia. The government's plan to move the National Capital (IKN) has made choices in some areas in East Kalimantan as the most ideal location. In terms of maritime affairs, the area of East Kalimantan borders the waters of the Indonesian Archipelago Sea Channel (ALKI) II. This is very strategic for connectivity chains, distribution and logistics lines in the archipelago and international sea transportation. This study aims to analyze the changes in the maritime side that must be done in order to prepare East Kalimantan as an IKN in the field of infrastructure, the title of the Navy's strength, and the strategies of various related agencies. The results of this study indicate that there is an increase in infrastructure, especially dock and port terminal facilities, and the addition of open storage for loading and unloading. In addition, PT. PELINDO IV Balikpapan includes plans to build a Military Base in the Company's Master Plan (RIP). Of course, this will greatly affect the title of force in the Indonesian Navy which is currently not able to fully support security operations in the region. Then, related agencies such as the Balikpapan Class I Port Authority and Office need to work together with other agencies to prepare East Kalimantan as the new National Capital.